Regenerative Braking Energy Recovery From a Platoon Powered by a DC Electric Road System - Saleh A. Ali; Volker Pickert; Mansoureh Zangiabadi; Mohammed A. Alharbi; Handong Li (IET Electrical Systems in Transportation)
Electric road systems (ERSs) are anticipated to be major energy consumers. The energy efficiency of an ERS can be significantly improved by implementing the practice of driving electric vehicles (EVs) in closely spaced platoons. This driving configuration effectively reduces the drag coefficient of all vehicles within the platoon, resulting in a substantial decrease in the power demanded from the grid. Moreover, it enables the collective recuperation of regenerative energy from braking EVs rather than feeding the individual braking energy into each vehicle battery. Recuperating energy is well understood from trains. To safeguard the network from overvoltage, braking resistors are commonly utilised in conjunction with a nearby energy storage system (ESS) or feeding power upstream into the AC grid via bidirectional substations. This paper utilises Simulink to model an ERS featuring two EV platoons (EVPs), simulating power flow within the system and assessing various technologies for regenerative energy recuperation. A control technique for efficient management of regenerative energy is introduced and validated through experiments by using dedicated software designed for emulating regenerative braking energy in DC railway applications.